1985
DOI: 10.1017/s0022172400062860
|View full text |Cite
|
Sign up to set email alerts
|

Antibody status to influenza A/Singapore/1/57(H2N2) in Finland during a period of outbreaks caused by H3N2 and H1N1 subtype viruses

Abstract: The incidence of haemagglutination inhibition (HI) antibody (titre greater than or equal to 12) to influenza A/Singapore/1/57(H2N2) in sera collected from a Finnish population in the summer of 1981 was 58%. Subjects born after 1968 were essentially seronegative, and a comparable low HI antibody status was also recorded among the elderly, the lowest being in people born during the period 1901-10. A small increase in antibody titre to the H2N2 virus was observed in the different age groups after infections with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The low levels of binding to DENV2 detected validated our hypothesis that these plasmablasts resulted from the reactivation of MBCs from a past DENV1 exposure, rather than as part of a naive response to the current DENV2 infection. OAS has been well described for antibody responses to repeated influenza virus exposures (47)(48)(49)(50), and a few reports have demonstrated this phenomenon in the secondary dengue virus B cell response, as well (29,51,52). Our data strongly suggest that OAS may play a role in the secondary dengue virus immune response and result in decreased binding affinity and neutralization potency against the infecting serotype.…”
Section: Discussionsupporting
confidence: 63%
“…The low levels of binding to DENV2 detected validated our hypothesis that these plasmablasts resulted from the reactivation of MBCs from a past DENV1 exposure, rather than as part of a naive response to the current DENV2 infection. OAS has been well described for antibody responses to repeated influenza virus exposures (47)(48)(49)(50), and a few reports have demonstrated this phenomenon in the secondary dengue virus B cell response, as well (29,51,52). Our data strongly suggest that OAS may play a role in the secondary dengue virus immune response and result in decreased binding affinity and neutralization potency against the infecting serotype.…”
Section: Discussionsupporting
confidence: 63%
“…We did not consider Յ4-fold antibody titer rises to be significant. However, some investigators interpret even a 2-fold rise in the titer of antibody against the first virus of a sequential infection to be evidence of OAS (50). Furthermore, some studies reported the occurrence of OAS without observing a boost in the response to the first virus in some instances (51) or without evidence of a diminished response to the second virus (50) in sequential infections.…”
Section: Discussionmentioning
confidence: 99%
“…H2N2 viruses established a stable presence in humans for 11 years and caused approximately 2 million deaths worldwide before they disappeared from human circulation following the emergence of the 1968 pandemic H3N2 virus (Simonsen et al, 1998). The reintroduction of the H2 subtype into the human population would pose a significant global health threat in a population where the majority of humans now lack anti-H2 hemagglutinin (HA) serologic immunity (Pyhala 1985; Webster 1997; Nabel et al, 2011). Avian influenza virus surveillance provides evidence for the continuing circulation of H2 viruses in wild migratory birds and poultry in live bird markets (Schafer et al, 1993; Piaggio et al, 2012; Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%